Digital finance and agri-food value chains: Case studies from Tanzania - Valerian, Judith (International Food Policy Research Institute, 2025)
Agriculture is vital to Tanzania's economic framework, significantly contributing to the country's gross domestic product (GDP). According to the ministerial report on the agriculture sector, the agriculture sector contributed 26.3 percent to national GDP in 2024, an increase from 26.2 percent in the previous year (MOA, 2025). It employed an average of 61.4 percent of the population, a slight decrease from 65.6 percent in 2023. Furthermore, agriculture provides 65 percent of essential raw materials for industries (MOA, 2024). Specifically, crop production recorded a growth rate of 4.2 percent in 2023, up from 2.7 percent in 2022, contributing 16.1 percent to national GDP, an increase from 15 percent in 2022 (MOA, 2024). Agriculture continues to play a critical role in ensuring food security, meeting 128 percent of domestic food demand in 2024 (MOA, 2025). Exports of agricultural products also saw substantial growth, reaching approximately USD 3.54 billion in 2023/2024, a significant increase from about USD 1.2 billion in 2019/2020 (MOA, 2025). Tanzania's agricultural transformation increasingly relies on modernizing agri-food value chains, especially those linking rural producers to growing urban and export markets, which are seeing a widening price gap. Value addition is essential for improving agricultural productivity and can take multiple forms. Hidayati et al. (2023) categorize value addition based on quality, safety, and market orientation, while emphasizing the importance of social factors such as job creation and food safety, alongside economic aspects such as sales, profitability, and environmental impacts. In agriculture, value addition involves transforming raw materials into finished products and by-products through processes such as drying, processing, packaging, and distribution. These activities enhance the market value of agricultural products, bolster economic growth through job creation, and contribute to food security. Consequently, maximizing value addition is crucial to fully leveraging the potential of Tanzania’s agricultural sector and translating it into measurable economic growth.